Intensitas dan Luas Serangan Beberapa Isolat Fusarium oxysporum f.sp. zingiberi pada Jahe Gajah - Hermawati Cahyaningrum; Nur Prihatiningsih; Soedarmono Soedarmono (Universitas Gadjah Mada, 2017)
Ginger is one of the spices and medicinal commodities which is cultivated in Indonesia. One of the obstacles encountered in the cultivation of ginger is the rhizome rot disease which is mainly caused by Fusarium oxysporum Schlecht f.sp. zingiberi Trujillo. This study is aimed to know the growth ability and virulence level of the isolates on ginger rhizome and plants. The research was conducted in the laboratory and in the screen house by using Complete Random Design consisted of 10 treatments and 4 replications. The parameters observed were growth ability of F. oxysporum f.sp. zingiberi, rhizome rot disease symptoms, incubation period, extensive decay and weight difference of the rhizomes. The results showed that F. oxysporum f.sp. zingiberi which was stored for 4 years in sterile soil medium was still capable to cause damage to the rhizome and plants. Incubation periods of rhizome decay and plant symptoms were from 3 to 11.5 and 55.5 to 68.5 days, respectively. The most virulent isolate was MSO1 with extensive decay of rhizome and the wilting intensity were 108.95 mm2 dan 33.88%, respectively. IntisariJahe merupakan salah satu komoditas rempah dan obat yang banyak dibudidayakan di Indonesia. Salah satu kendala yang dihadapi dalam budidaya jahe adalah adanya gangguan penyakit busuk rimpang yang disebabkan (terutama) oleh Fusarium oxysporum Schlecht f.sp. zingiberi Trujillo. Penelitian bertujuan untuk menguji daya tumbuh dan virulensi isolat F. oxysporum f.sp. zingiberi pada rimpang dan tanaman jahe gajah. Penelitian dilakukan di laboratorium dan di rumah kasa menggunakan Rancangan Acak Kelompok Lengkap (RAKL) yang masing-masing terdiri dari 10 perlakuan dan 4 ulangan. Parameter yang diamati meliputi daya tumbuh F. oxysporum f.sp. zingiberi, gejala penyakit busuk rimpang, masa inkubasi, luas pembusukan dan selisih bobot basah rimpang. Hasil penelitian menunjukkan bahwa F. oxysporum f.sp. zingiberi yang telah di simpan 4 tahun dalam medium tanah steril mampu menyebabkan kerusakan pada rimpang dan tanaman jahe. Masa inkubasi gejala busuk pada rimpang serta gejala pada tanaman masing- masing berkisar antara 3–11,5 serta 55,5–68,5 hari. Isolat yang paling virulen adalah MSO1 dengan nilai luas pembusukan pada rimpang dan intensitas penyakit masing-masing sebesar 108,95 mm2 dan 33,88%.